TRANSFORMATIONAL LEADERSHIP IN BENOWO DISTRICT, SURABAYA CITY - Denny Christupel Tupamahu (DIA: Jurnal Administrasi Publik, 2023)
The aim of the research is to analyze the implementation of the Camat's transformational leadership; analyzing the supporting and inhibiting factors, as well as evaluating the impact of the implementation of the transformational leadership of the Camat in Benowo District, Surabaya City. This study uses a qualitative descriptive approach to analyze the transformational leadership of the Camat in Benowo District, Surabaya City. The research subjects consisted of sub-district and sub-district officials, as well as representatives of community leaders. The research subjects were selected from people who often interact with the sub-district head of Benowo sub-district, Surabaya city. Data collection was carried out by means of in-depth interviews and checking the validity of the data through source triangulation. Research data were analyzed using qualitative data analysis according to Creswell. The conclusions obtained are: 1) The transformational leadership of the Camat in Benowo District, Surabaya City is implemented by making himself a role model, realizing the vision and mission, stimulating employees to be innovative and creative, and providing fair and personal attention; 2) Supporting factors include work experience, education level, optimistic and friendly attitude, and employee support, while inhibiting factors include: low work motivation, low competence, limited number of human resources, and high workload; 3) The impact of implementation is reflected in the better quality of service and the increased contribution of employees in providing suggestions about their creativity in meetings that discuss innovation related to service to the community.